Supplier Performance Evaluation on Regular Raw Material Suppliers by Applying AHP and TOPSIS Approaches (Evidence from the Apple Agroindustry) - Afrizal Wisnu Wardana; Silvana Maulidah; Anisa Aprilia (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2022)
The supplier is one of the supply chain entities that serves as a provider of raw materials, and poor supplier performance will harm the company's smooth production system. This study aims to identify supplier criteria, analyze priority weights, and evaluate supplier performance in the apple Agro-industry. Respondents in this study were business owners chosen through the judgmental sampling method. The Analytical Hierarchy Process (AHP) method was used to test the priority weights of supplier performance criteria, while the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method was used to test the priority weights of supplier performance priorities. The results showed that the service criteria received the highest priority weighting criteria, followed by price, quality, and delivery. Good service will positively impact integration, making it easier to achieve an effective and efficient supply chain. Meanwhile, in terms of the company's fixed supplier performance priorities, supplier 1 received the highest rating, followed by suppliers 2 and 3. Thus, supplier performance is quite good, but several things could be improved, specifically fruit size and responsiveness to supplier 3 and prices to suppliers 1 and 2.